Slower diffusion and anomalous association of R453W lamin A protein alter nuclear architecture in AD-EDMD. Issue 49 (9th November 2022) - Mukherjee, Chandrayee; Sengupta, Duhita; Maganti, Lakshmi; Mahendar, M.; Bhattacharyya, Dhananjay; Sengupta, Kaushik
Abstract : Changes in the microdynamics landscape of Ig fold R453W modulate the mobility and assembly of full length lamin A. Abstract : Lamins maintain the shape and rigidity of the nucleus in the form of a proteinaceous scaffold underneath the inner nuclear membrane (INM) and provide anchorage to chromatin and other nuclear proteins. Mutations in the human LMNA gene encoding lamin A/C cause about 16 different diseases with distinct phenotypes collectively termed as laminopathies which affect primarily the muscle tissues as well as adipose tissues, neuromuscular junctions and multiple other organs in progeroid syndromes. Lamins contain several domains of which Ig-fold is one of the well characterized and structured domains that harbours many mutations leading to deleterious interactions with other nuclear proteins. In this work, we have elucidated the effects of 3 such mutations namely R453W, W498C and W498R on the dynamics and flexibility of the Ig-fold domain and the consequent effect on the assembly into lamina by live cell imaging, fluorescence correlation spectroscopy (FCS) and molecular dynamics (MD) simulations. From our simulation studies, we concluded that R453W exhibits the highest fluctuation at the residues 475 and 525 in the Ig fold domain compared to the wild type and other mutants. This resulted in pronounced random self-association which could be corroborated by lower diffusivity values obtained from FCS. This is the first report where such an alteration in the full length has been documented by gross changes in diffusional properties as a sequel to a mutation in the Ig fold domain.